Decision making and executive functions in problematic pornography use - Müller, Silke M.; Antons, Stephanie (Frontiers in Psychiatry, 2023)
Introduction Previous research on cognitive functions in Compulsive Sexual Behavior Disorder (CSBD) and problematic pornography use (PPU) reported inconsistent findings and mostly included sexual pictures in the used tasks. The role of general executive functions and cognitive competences (without the presence of appetitive stimuli) in the context of PPU is largely unexplored. Methods This study investigated differences between individuals with high versus low problem severity of PPU regarding decision making and executive functions. The sample of the laboratory study consisted of N = 102 male adults. Besides measures of trait impulsivity, we used standard neuropsychological tests (Trail Making Test and three-back working memory task) and an intertemporal risky choice paradigm, the Cards & Lottery Task (CLT). Results The results show heightened impulsivity (urgency and deficits in perseverance) in individuals with high PPU, but no differences regarding performance in the CLT and executive function tasks. Discussion The findings indicate that PPU might be associated with impulsive behavior when experiencing strong emotions (urgency) and deficient cognitive performance especially in the presence of sexual stimuli but not in general.